levels of Sportive tourism elements in Tartous city and the activities contributing to its development (Journal of Hama University, 2026)
This research aims to explore the level of sportive tourism elements in Tartous city and studying the differences among them, in addition to explore the level of sportive activities which contribute to develop the sportive tourism in this city and define the most important sportive activity which contribute in its development.  It has been used the descriptive approach using questionnaire, which has been applied at a sample of (68) workers from Tartous governorate, directorate of tourism and sportive union in Tartous governorate. The results showed that the level of sportive tourism elements in Tatrtous city is middle, and the natural potentials from tourism elements contributes more than the human and material elements in developing the sportive tourism in this city. Also, the results showed very good level for the activities of aquatics and they contributes the most from the rest of the sportive activities in developing the sportive tourism in Tartous city.